The Link Between Endoplasmic Reticulum Stress and Lysosomal Dysfunction Under Oxidative Stress in Cancer Cells - Mariapia Vietri; Maria Rosaria Miranda; Giuseppina Amodio; Tania Ciaglia; Alessia Bertamino; Pietro Campiglia; Paolo Remondelli; Vincenzo Vestuto; Ornella Moltedo (Biomolecules, 2025)
Lysosomal dysfunction and endoplasmic reticulum (ER) stress play essential roles in cancer cell survival, growth, and stress adaptation. Among the various stressors in the tumor microenvironment, oxidative stress (OS) is a central driver that exacerbates both lysosomal and ER dysfunction. In healthy cells, the ER manages protein folding and redox balance, while lysosomes regulate autophagy and degradation. Cancer cells, however, are frequently exposed to elevated levels of reactive oxygen species (ROS), which disrupt protein folding in the ER and damage lysosomal membranes and enzymes, promoting dysfunction. Persistent OS activates the unfolded protein response (UPR) and contributes to lysosomal membrane permeabilization (LMP), leading to pro-survival autophagy or cell death depending on the context and on the modulation of pathways like PERK, IRE1, and ATF6. Cancer cells exploit these pathways by enhancing their tolerance to OS and shifting UPR signaling toward survival. Moreover, lysosomal impairment due to ROS accumulation compromises autophagy, resulting in the buildup of damaged organelles and further amplifying oxidative damage. This vicious cycle of ROS-induced ER stress and lysosomal dysfunction contributes to tumor progression, therapy resistance, and metabolic adaptation. Thus, targeting lysosomal and ER stress responses offers potential as cancer therapy, particularly in increasing oxidative stress and promoting apoptosis. This review explores the interconnected roles of lysosomal dysfunction, ER stress, and OS in cancer, focusing on the mechanisms driving their crosstalk and its implications for tumor progression and therapeutic resistance.